Indoor wireless positioning - Yong, Alex (2018)
Indoor Wireless Positioning (IWP) is important to localize and assists in navigating a mobile node wirelessly in an indoor environment. IWP will be greatly useful and common in people’s daily lives, especially in modern cities like Singapore that are densely populated and packed with big malls and buildings due to lack of space where most of the people will have their activities indoor. IWP will become more popular and demanding for those who need to navigate within the big malls looking for direction such as Modern warfare where indoor war fighting more commonly in urban area to emergency situations for rescue team to evacuate or for search and rescue mission. Commercial and leisure purpose could also benefit from IWP for easy location and navigate to retails and services shops in big malls. Although Global Positioning System (GPS) is widely and commonly used but it will not work in indoor environment due to heavy signal attenuation and multipath. The ultimate goal will be GPS and IWP be integrate seamlessly to further expand the accuracy of the position in all places and environment. The objective for this project is to design a system that works in an indoor environment to provide localization information for navigation service similar to the outdoor GPS through applying localization algorithm. The purpose of this project is for me to show my understanding of the problem that we face in our current situation and how this project can actually solve or even improve the situation.